Production of a Recombinant Anti-tyrosinase Chimeric Peptide in Methylotrophic Yeast, Pichia pastoris - Rani, J. Usha; Pasha, Chand; Vutukuru, S.S.; Prasad, B. Siva (International Journal of Scientific Research in Biological Sciences, 2019)
In recent years, application of peptides increased as therapeutic agents due to their high activity per unit mass, highly specific and low toxicity. Pichia pastoris (P. pastoris) is a substantial workhorse in pharmaceutical biotechnology, especially for heterologous peptide production. Hence, a recombinant antityrosinase peptide that is vital for formulating skin lightening agents is carried out in the present study. P. pastoris X33was employed in chimeric peptide expression and production. Coding gene (669 bp) encoding for a protein of small peptides separated with NG 223 amino acid having antityrosinase activity was cloned into pPICZα vector. Zeocin based selection of transformants was conducted in YEPD medium. The recombinant plasmid was isolated and digested with Sal I. Subsequently, it was transformed by electroporation and expressed under the control of the AOX1 promoter in P. pastoris X33. His Tag based approach (Ni-Agarose) was used to purify the recombinant peptide. The purified recombinant chimeric peptide (25 kDa) was characterized using SDS-PAGE. The culture when induced with 0.5% (v/v) methanol average yield was 40 mg/mL for 72h. The chimeric peptide was digested with hydroxyl amine and peptide cocktail purified by size exclusion chromatography. Antityrosinase potential of cocktail of purified peptide fractions was 62%. The recombinant chimer peptide characterized in the study can be used as a proxy in formulating skin lightening agents.